Effects of 2% dehydration on lactate concentration during constant-load cycling - Green, J. M.; Miller, B.; Simpson, J.; Dubroc, D.; Keyes, A.; Neal, K.; Gann, J.; Andre, T. (The Journal of Strength and Conditioning Research, 2018)
The lactate [La] threshold (LT) can predict endurance performance potential. Dehydration may alter LT. This study examined effects of dehydration on [La] response during constant-load cycling. Recreationally fit (VO2peak = 48.7 ± 5.2 ml/kg/min) male participants (n = 9) completed 2 × 40-minute constant-load cycling trials; euhydrated (HYD) and after previous evening passive (water bath) dehydration (2% body weight, DEH) (HYD and DEH counterbalanced). Lactate, heart rate (HR), 10-point Omni ratings of perceived exertion (RPE), and rectal temperature (Trec) were measured after warm-up (WU) and at 10, 20, 30, and 40 minutes. Before cycling, urine specific gravity (USG) was measured and participants estimated perceived recovery status (PRS). Urine specific gravity DEH (1.027 ± 0.004) was significantly greater than HYD (1.013 ± 0.007). After WU, [La] was significantly greater (all time points) for DEH (~4.1 mmol/L) vs. HYD (~3.5 mmol/L) with similar results for HR (DEH: ~167, HYD: ~158 b/min). For DEH, RPE was significantly greater (~1 unit) at 20, 30, and 40 minutes, and Trec was significantly greater at 30 and 40 minutes (~0.4° C). DEH (vs. HYD) also resulted in significantly different resting HR (93 ± 6, vs. 85 ± 7 b/min), significantly greater session RPE (7.7 ± 1.1 vs. 5.3 ± 1.1), and significantly lower subjective feelings of recovery (PRS = 6.4 ± 2.9, vs. 9.0 ± 1.5). Current results indicate systematic changes in [La] and associated physiological responses result from previous day dehydration. Hydration status should be a concern in paradigms where [La] assessment is used.